2016
DOI: 10.1016/j.scitotenv.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Solid-solution partitioning and thionation of diphenylarsinic acid in a flooded soil under the impact of sulfate and iron reduction

Abstract: • We first investigated the solid-solution partitioning of DPAA in a flooded soil.• We first examined the impacts of sulfate and iron reduction on DPAA partitioning.• Elevated DPAA mobilization and thionation was observed in sulfide soil.• DPAA mobilization associated with Fe(III) reductive dissolution was demonstrated.• Enhanced mobilization of DPAA and sulfate reduction promoted DPAA thionation. Editor: Jay Gan Diphenylarsinic acid (DPAA) is a major organic arsenic (As) compound derived from abandoned chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…These results provide a means of estimating the DPAA sorption capacity of clay mineral fractions on the basis of DPAA fractions associated with amorphous, poorly crystalline, and well-crystallized Fe/Al (hydr)oxides. It should also be noted that DPAA extracted in steps iii-iv could be a potential source of DPAA contamination during the dissolution of Fe (hydr)oxides in flooded soils (Zhu et al 2016b). According to our SEP data, a substantial amount of DPAA in the clay mineral fractions from the Gleyic Acrisol soil (46.2%) was presented in this potentially available form (Fig.…”
Section: Dpaa Speciation In Clay Mineral Fractionsmentioning
confidence: 63%
“…These results provide a means of estimating the DPAA sorption capacity of clay mineral fractions on the basis of DPAA fractions associated with amorphous, poorly crystalline, and well-crystallized Fe/Al (hydr)oxides. It should also be noted that DPAA extracted in steps iii-iv could be a potential source of DPAA contamination during the dissolution of Fe (hydr)oxides in flooded soils (Zhu et al 2016b). According to our SEP data, a substantial amount of DPAA in the clay mineral fractions from the Gleyic Acrisol soil (46.2%) was presented in this potentially available form (Fig.…”
Section: Dpaa Speciation In Clay Mineral Fractionsmentioning
confidence: 63%
“…Concurrently, the K f values decreased for most soils deficient of amorphous and crystalline metal (hydr)oxides with the removal of SOM but increased slightly for those of S2, S7 and S10 (Table 2). Many discrepancies in the role of SOM in the sorption of phenyl As have been reported and factors related to the role of SOM, namely competitive sorption (Zhu et al, 2016a), covering sorption sites on Fe/Al (hydr) oxides (Maejima et al, 2011), forming SOM-Fe-As complexes (Fu et al, 2016) and hydrophobic interactions (Arroyo-Abad et al, 2011) should be considered, and the contribution of each factor to the sorption of phenyl As may depend on soil type.…”
Section: Resultsmentioning
confidence: 99%
“…The soil incubation experiment was prepared using 100-mL serum bottles as described by Zhu et al (2016a). Soil cultures containing 20 g of the dried soil and 30 mL of the ultrapure water were prepared for anoxic and sulfide incubation.…”
Section: Soil Incubation Experimentsmentioning
confidence: 99%
“…These results demonstrate that DPAA sorption onto soils are due mainly to ligand exchange reactions with hydroxyl groups on Fe (hydr)oxides. Limited studies have found that DPAA mobilization in a biostimulated Phaeozem was due primarily to the addition of sodium lactate at early stages but due to the near-complete Fe(III) reduction at later stages of incubation (Zhu et al 2016a). Other studies propose that As mobilization is attributable mainly to Fe(III) reduction in carbon-limited environments (Masscheleyn et al 1991;Nickson et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation